Outcomes of Extended Pedicle Technique vs Free Nipple Graft Reduction Mammoplasty for Patients With Gigantomastia. (26th September 2022) - Talwar, Ankoor A; Copeland-Halperin, Libby R; Walsh, Landis R; Christopher, Adrienne N; Cunning, Jessica; Broach, Robyn B; Baratta, Michael D; Copeland, Michelle; Shankaran, Vidya; Butler, Paris D
Abstract: Background: Optimal reduction mammoplasty techniques to treat patients with gigantomastia have been debated and can involve extended pedicles (EP) or free nipple grafts (FNG). Objectives: The authors compared clinical, patient-reported, and aesthetic outcomes associated with reduction mammoplasty employing EP vs FNG. Methods: A multi-institutional, retrospective study of adult patients with gigantomastia who underwent reduction mammoplasty at 2 tertiary care centers from 2017 to 2020 was performed. Gigantomastia was defined as reduction weight >1500 g per breast or sternal notch-to-nipple distance ≥40 cm. Surgeons at 1 institution employed the EP technique, whereas those at the other utilized FNG. Baseline characteristics, preoperative and postoperative BREAST-Q, and clinical outcomes were collected. Aesthetic outcomes were assessed in 1:1 propensity score-matched cases across techniques. Preoperative and postoperative photographs were provided to reviewers across the academic plastic surgery continuum (students to faculty) and non-medical individuals to evaluate aesthetic outcomes. Results: Fifty-two patients met the inclusion criteria (21 FNG, 31 EP). FNG patients had a higher incidence of postoperative cellulitis (23% vs 0%, P < 0.05) but no other differences in surgical or medical complications. Baseline BREAST-Q scores did not differ between groups. Postoperative BREAST-Q scores revealed greater satisfaction with the EP technique ( P < 0.01). The aesthetic assessment of outcomes in 14 matched pairs of patients found significantly better aesthetic outcomes in all domains with the EP procedure ( P < 0.05), independent of institution or surgical experience. Conclusions: This multi-institutional study suggests that, compared with FNG, the EP technique for reduction mammoplasty provides superior clinical, patient-reported, and aesthetic outcomes for patients with gigantomastia. Level of Evidence: 4: